Cloning and expression of a functionally active truncated N-glycosylated KSHV complement regulatory protein and immunohistochemical studies with the anti-KCP peptide antibody - Gomes Pereira, Neuza Alexandra (Division of Virology, 2017)
Kaposi sarcoma herpes virus (KSHV) is a typical DNA virus that is associated with a number of proliferative diseases including Kaposi's sarcoma. The KSHV open reading frame (ORF) 4 encodes a complement regulatory protein (Kaposi complement-binding protein, KCP) that binds complement proteins and inhibits the complement-mediated lysis of cells infected by the virus, thus providing a strategy for evasion of the host complement system. Kaposi's sarcoma is an angiogenic skin lesion that has been recognized as one of the most abundant tumours found in many parts of Southern Africa and which can occasionally become highly invasive, aggressive and capable of causing death, particularly amongst AIDS patients. It is of major significance to understand how complement control proteins (CCPs) such as KCP perform their biological functions at the molecular and structural levels, because of their potentials as therapeutic agents, their implications in the pathology and importance in the etiology of many disease conditions. This study was therefore undertaken to characterise the structure-function relationship of KCP. Based on primary sequence analysis and comparison to other functionally and structurally similar proteins, oligonucleotide primers were designed to amplify by PCR, three regions of the predicted ORF 4 from human herpes virus-8 (llliV-8) DNA isolated from a primary effusion lymphoma cell line. The PCR products were inserted by ligation into the expression vector pPIC9 to generate three recombinant plasmids for heterologous expression in the yeast, Pichia pastoris and to produce separately, the 4 N-terminal Sushi domains (KCP-S, small), KCP protein lacking the putative transmembrane binding domain (KCP-M, medium) and the full-length protein (KCPF, full). Expression of the viral proteins was confirmed by SDS-PAGE and Western blot analyses using a rabbit polyclonal antibody directed against a selected peptide region that is common to all three recombinant KCPs. All the KCP proteins migrated electrophoretically as higher bands compared to their expected sizes. The lower mobilities of the proteins may be due to g1ycosy1ation since there are potential N-and O-glycosylation sites in the protein's primary sequence. Also, diffused bands were obtained in all the electrophoretic gels and Western blots carried out, which is characteristic of glycoproteins. Furthermore, the antibody recognized several larger and smaller bands that may represent aggregates and/or degradation products respectively. Both partially purified KCP-S and KCP-S directly from expression media were able to inhibit complement-mediated lysis of sensitized sheep erythrocytes by approximately 60% in a hemolysis assay. This result confirms previous reports that recombinant KCP is twice more efficient in inhibiting the classical pathway-mediated lysis of erythrocytes than the vaccinia virus complement control protein (VCP), which also contains 4 Sushi domains. The KCP-F and KCP-M proteins did not show any significant complement inhibitory activities. Preliminary immunohistochemical studies using the same antibody were carried out to determine the expression and distribution of KCP proteins in Kaposi's sarcoma.